2020
DOI: 10.1177/1359105320922298
|View full text |Cite
|
Sign up to set email alerts
|

Associations between specific physical activity domains and social isolation in 102,072 Brazilian adolescents: Data from the 2015 National School–Based Health Survey

Abstract: This study investigated the association among loneliness, number of friends, and participation in physical education classes, leisure-time physical activities, and active commuting. Data from 102,072 adolescents participating in the National School–based Health Survey aged 11–19 years were analyzed. Information about the study variables was self-reported through a questionnaire. Adolescents more active in physical education classes and leisure were less likely of having social isolation. Those more active in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
1
7
0
2
Order By: Relevance
“…W. Liu et al, 2020). The possible association between not attending physical education and loneliness has also been found in a study among adolescents in Brazil (Santos et al, 2020), and may be attributed to lower socializing experiences when not attending physical education classes.…”
Section: Discussionsupporting
confidence: 58%
“…W. Liu et al, 2020). The possible association between not attending physical education and loneliness has also been found in a study among adolescents in Brazil (Santos et al, 2020), and may be attributed to lower socializing experiences when not attending physical education classes.…”
Section: Discussionsupporting
confidence: 58%
“…Vancamfort et al [27] found an association between physical inactivity and higher odds for feeling lonely in a cross-sectional study with a large sample of adolescents aged between 12 and 15 years. Dos Santos et al [34] found in their large national school-based health survey among Brazilian adolescents that more active adolescents were less likely to experience social isolation. The nature of the causal link still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Participation in physical and social activities may improve patients’ disease severity and well-being, respectively, and lack thereof may worsen disease outcomes and contribute to feelings of isolation [ 6 , 7 ]. Social anxiety may be a contributing factor to HS patients’ degree of isolation.…”
Section: Discussionmentioning
confidence: 99%